2002
DOI: 10.1530/rep.0.1240235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EDTA saturated with Ca2+ (Ca-EDTA) on pig, bovine and mouse oocytes at the germinal vesicle stage during maturation culture and the involvement of chelation of Zn2+ in pronuclear formation induction by Ca-EDTA

Abstract: Preovulatory mammalian oocytes at the germinal vesicle (GV) stage, when removed from follicles, can spontaneously undergo meiotic maturation in culture, resulting in secondary oocytes arrested at metaphase of the second meiotic division (MII). The duration of the period required for the meiotic maturation of mammalian oocytes in culture varies depending on the species: in mice, cattle and pigs it is about 12, 24 and 48 h, respectively. During the meiotic maturation period, there are two distinct successive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The ultrastructural features of collagen in EDTA-and PA-demineralized dentin beams were found to be similar for both groups (17). As EDTA has been shown to be an effective Zn 2+ and Ca 2+ chelator (27), it was expected to inhibit MMP activity. However, EDTA (or Ca-EDTA) has to be present in excess, relative to Zn 2+ , for the chelating efficiency of EDTA to be observed (27).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The ultrastructural features of collagen in EDTA-and PA-demineralized dentin beams were found to be similar for both groups (17). As EDTA has been shown to be an effective Zn 2+ and Ca 2+ chelator (27), it was expected to inhibit MMP activity. However, EDTA (or Ca-EDTA) has to be present in excess, relative to Zn 2+ , for the chelating efficiency of EDTA to be observed (27).…”
Section: Discussionmentioning
confidence: 83%
“…As EDTA has been shown to be an effective Zn 2+ and Ca 2+ chelator (27), it was expected to inhibit MMP activity. However, EDTA (or Ca-EDTA) has to be present in excess, relative to Zn 2+ , for the chelating efficiency of EDTA to be observed (27). In our study, most traces of EDTA were removed from dentin by extensive rinsing with water, so there was no residual EDTA in EDTA-demineralized dentin beams to inhibit the activity of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…EDTA-demineralized dentine presented MMP collagen degradation values similar to those of PA-demineralized dentine [Osorio et al, 2011b]. It may be that EDTA (or calcium EDTA) has to be present in excess in order to be an effective zinc and calcium chelator [Azuma et al, 2002]. However, both substances lost their effect after 24 h, probably due to precipitation in the presence of cations derived from simulated body fluids [Di Palma et al, 2003;Zerella et al, 2005].…”
Section: Discussionmentioning
confidence: 90%
“…Ethylenediaminetetraacetic acid (EDTA) has been shown to be an effective zinc and calcium chelator [Azuma et al, 2002]. However, EDTA-demineralized dentine presented MMP collagen degradation values similar to those of phosphoric acid (PA)-demineralized dentine [Osorio et al, 2011b].…”
mentioning
confidence: 99%
“…In addition, the membrane concentration gradient established by the ion transmembrane transport provides the energy source for a series of cell metabolic activities. In many cation transmembrane transport activities, the transport of calcium and zinc ions plays an important role in the regulation of ooctye maturation [ 33 – 35 ]. In this study, the enrichment of cation transmembrane transport-related GO categories confirmed that a different regulation of ion-transmembrane transport exists in yak ovaries compared with cattle ovaries, but its exact function requires further study.…”
Section: Resultsmentioning
confidence: 99%